Josef Paneth correspondence - Paneth, Josef
Letters (1884 February 4 and 1884 March 30) from Paneth to his uncle concerning Paneth's friendship with Friedrich Wilhelm Nietzsche and his assessment of Nietzsche's work.
Typewritten transcripts.
Physiologist.
In German.
Forms part of: Sigmund Freud collection.
Keywords: Nietzsche, Friedrich Wilhelm, -- 1844-1900.; Philosophy; Physiologists